1986
DOI: 10.1111/j.1471-0528.1986.tb07881.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of extremely‐low‐birthweight infants

Abstract: Summary. The overall 1‐year survival rate of 261 infants born at 500 g–999 g over a 7‐year period was 46%. The survival rate of the 220 inborn infants, corrected for birth defects, would have increased from 47% to 57% if delivery room deaths were excluded and to 62% if postneonatal deaths had also been ignored. Survival improved progressively with increasing 100 g weight groups. The disability rate in the 108 survivors who were at least 2 years old corrected for prematurity was 28% with little variation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…1213 Survival data in extremely preterm infants are more variable with respect to gestational age than with respect to birthweight. 12 This is not surprising in view of the previously mentioned inherent inaccuracies in conventional gestational age assignment. After delivery, gestational age assignment in severely preterm infants, less than 27 weeks, is fraught with even more difficulty, since no such postnatal "gold standard" exists, and is at best an educated guess.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…1213 Survival data in extremely preterm infants are more variable with respect to gestational age than with respect to birthweight. 12 This is not surprising in view of the previously mentioned inherent inaccuracies in conventional gestational age assignment. After delivery, gestational age assignment in severely preterm infants, less than 27 weeks, is fraught with even more difficulty, since no such postnatal "gold standard" exists, and is at best an educated guess.…”
Section: Discussionmentioning
confidence: 96%
“…In these settings, neonatal mortality exceeds 50%. 11,12,19 What determines the variability of physician response is unclear. Goldenberg and coworkers 21 suggested that obstetric management often appeared to be based on inaccurate information about neonatal survival.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies showed that the survival rate of inborn ELBW infants would have increased from 47 to 57% if delivery room deaths had been excluded and the study was restricted to NICU admissions. 6 The survival rate would have increased further to 62% if neonatal survival was reported instead of 1-year survival. There is an increased risk of rehospitalization after discharge from severe respiratory illnesses.…”
Section: Institution-based Studiesmentioning
confidence: 97%
“…Infants born weighing < 2500 g at birth are termed low birth weight (LBW), those weighing < 1500 g are termed very-low birth weight (VLBW) and those weighing < 1000 g are referred to as extremely-low birth weight (ELBW; World Health Organization, 1961). Survival rates of ELBW infants increased from 10-20 % in the 1960s, to approximately 40-70 % in the 1980s (Yu et al 1986). Prematurity accounts for at least 75 % of early infant deaths; however, the survival of those infants has improved greatly, and subsequently their quality of life has improved dramatically.…”
Section: Premature Birthmentioning
confidence: 99%